Mbolo Weki of Mbojo Tribe: Discussion Culture for Cooperative Learning Model for Elementary School Students - Anisaturahma; Nizaar, Muhammad; Haifaturrahmah (Journal of Education Reseach and Evaluation, 2025)
Indonesia is known as a country with various ethnicities and cultures, but currently, the distinctive culture of each region is starting to be forgotten by the younger generation. This research aims to reveal the discussion values contained in each stage of the mbolo wiki activity. These values are then used to design a cooperative learning design for elementary school students. This research used a descriptive qualitative approach. Data collection techniques used in-depth interviews, observations, and documentation. This research used an interactive model data analysis technique. The results showed that generally, students are quite interested in cooperative learning that has harmony with Mbolo Weki activities.Meanwhile, there is no difference between cooperative learning and Mbolo Weki activities. This research also shows that there is a strong alignment between mbolo weki activities and cooperative learning principles. Mbolo Wiki prioritizes the principles of togetherness and mutual respect in deliberation. The results of this study have implications for cultural internalization that are still implemented by the surrounding community in the learning process in the classroom. The traditional values of mbolo weki are very similar to group discussion activities in cooperative learning.